Hubungan Pengetahuan Dengan Pengelolaan Obat Yang Tepat Di Kelurahan Sabaru Kota Palangka Raya Kalimantan Tengah - Nindi Kristiani; Melviani Melviani; Esti Yaundari (LPPM Universitas Sari Mulia, 2021)
Introduction: Drug abuse in the community occurs due to a lack of knowledge about how to use drugs, this is supported by a lack of knowledge related to drug management starting from how to get, use, store and dispose of drugs. Drug management can be influenced by knowledge, if the knowledge is high then the ability to manage drugs by the community will be higher. Objective: This study was conducted with the aim of knowing the relationship between knowledge and drug management. Methods: This research method is a cross sectional observational study with a quantitative approach. The number of samples in this study were 50 respondents with a sampling technique that is purposive sampling with data collection carried out using a google form questionnaire. The data were analyzed using the Spearman rank test. Results: The results of this study were that 34 respondents (68%) had sufficient knowledge (56%-75%) and 39 respondents (78%). There is a relationship between knowledge and drug management with a value of value = 0.000 which means 0.000 <0.05 and based on the correlation coefficient value of 0.616, it shows a strong and unidirectional strength between knowledge and drug management in Sabaru Village. Conclusion: There is a significant relationship between knowledge and drug management in Sabaru Village.